Home Based Businesses in Australia:A Review of the Literature - Jay, Leighton (2003)
In Australia, small-to-medium sized businesses (SMEs) make a significant contribution to the health and success of the national economy and represent 96% of all firms. These businesses can be divided into three very distinct groups based on the number of employees. Medium enterprises usually have between 20-200 employees; small businesses have 5-19 staff; and micro-businesses are those employing less than five staff, including self-employed individuals (Australian Bureau of Statistics (ABS) 2000).Of the one million plus SMEs that were operating in Australia in June 2001, an estimated 778 400, or 67%, were identified as home-based businesses (HBBs) (ABS 2001). Based on these figures, the HBB sector represents more than half of all businesses in Australia. It is a significant sector within the Australian business community, yet suffers from a low profile and is generally poorly understood. While there are significant gaps in the current level of knowledge about HBBs, there is growing evidence highlighting their importance to Australia's overall economic performance. Recent studies show that micro-enterprises provide the greatest source of future immediate job creation (ABS 1997; Department of Employment Workplace Relations & Small Business (DEWRSB) 1998), and that the majority of new firms start as home-based businesses (Peacock 2000).HBBs are a growing phenomenon in Australia, with several Australian studies indicating that they are both viable long term businesses, and more than the marginal financial enterprises they were thought to be a decade ago (Stanger 2001; Peacock 2000). Ongoing changes in employment practices combined with broad social changes are likely to lead to a continuing growth in the size of this sector. Dawson & Turner's (1989) oft-quoted study of the causes leading to the growth of home-based work identifies factors such as new technologies,economic conditions and lifestyle choices as being key factors in the rise of the phenomenon of home-based work.Although their study includes home-based employees and earlytelecommuters, it provides an early indication of the development and growth of the HBB sector.